TECHNOLOGICAL ANALYSIS OF FLAT SURFACE CONDITIONS BY MAGNETIC ABRASIVE FINISHING METHOD (MAF) (Journal of Engineering, 2011)
This study introduced the effect of using magnetic abrasive finishing method (MAF) for finishing flatsurfaces. The results of experiment allow considering the MAF method as a perspective for finishing flatsurfaces, forming optimum physical mechanical properties of surfaces layer, removing the defective layersand decreasing the height of micro irregularities. Study the characteristics which permit judgment parameters of surface quality after MAF method then comparative with grinding.